Single-material-based anomalous Nernst thermopile driven by solar heating and radiative cooling. (1st September 2022) - Chiba, Naoki; Ishii, Satoshi; Modak, Rajkumar; Uchida, Ken-ichi
Abstract: We report a proof-of-concept demonstration of the anomalous Nernst thermopile driven by solar heating and radiative cooling. The anomalous Nernst thermopile proposed here consists of a zigzag-shaped single magnetic material without any junction structures and black ink-coated alternately on the wires arranged in the zigzag configuration. The voltage generated from this structure increases by an order of magnitude compared to an uncoated structure under the condition with solar heating and radiative cooling, which can further be enhanced by increasing the number of wires. This device concept paves the way for outdoor thermoelectric applications based on the anomalous Nernst effect.